RANCANG BANGUN APPLICATION PROGRAMMING INTERFACE MENGGUNAKAN GRAPHQL PADA MULTIPLATFORM APPLICATION - Gede Humaswara Prathama; I Gusti Ngurah Darma Paramartha (Jurnal Teknologi Informasi dan Komputer, 2022)
ABSTRACTDuring the last decade the use of APIs has become a mandatory service for web-based applicationdevelopment, in addition to using APIs for communication between applications and database servers,APIs are also used as communication between applications to share data with each other in the B2B(Business to Business) concept. In the current API development, RESTful and SOAP architectures stilldominate where RESTful produces JSON data format and SOAP produces XML data format. In thecurrent development of applications where the use of APIs is used by various platforms such as web,mobile, desktop, smartwatch, IoT devices and other platforms in the same application or data so thatAPI developers who utilize RESTful or SOAP architecture create many versions and API nodes to serveAPI requests from each of these platforms. Not a few developments with limited resources that do notcreate versions or API nodes for each platform at the expense of the performance of the API responseboth from latency, bandwidth and data provided. This research will apply GraphQL architecture indeveloping APIs that are able to serve applications from various platforms, GraphQL can overcomeproblems related to available data and application requirements, minimal use of latency and bandwidthaccording to the needs of each platform as well as documentation and version problems of the API byutilizing the features provided on the GraphQL architecture.Keywords: GraphQL, Multi-platform, API, RESTful, latency, bandwidth.ABSTRAKSelama dekade terakhir penggunaan API menjadi layanan yang wajib disediakan dalam pengembanganaplikasi berbasis web, selain pemanfaatan API untuk komunikasi antara aplikasi dengan database server,API juga dimanfaatkan sebagai komunikasi antar aplikasi untuk saling berbagi data dalam konsep B2B(Business to Business). Dalam pengembangan API saat ini arsitektur RESTful dan SOAP masihmendominasi dimana RESTful menghasilkan format data JSON dan SOAP menghasilkan format databerbentuk XML. Dalam perkembangan aplikasi saat ini dimana penggunaan API digunakan berbagaimacam platform seperti web, mobile, desktop, smartwatch, IoT devices dan platform lain dalam satuaplikasi atau data yang sama sehingga pengembang API yang memanfaatkan arsitektur RESTful atauSOAP membuat banyak versi dan node API untuk melayani permintaan API dari masing-masingplatform tersebut. Tidak sedikit pengembangan dengan keterbatasan resource yang tidakmengkhususkan versi atau node API untuk masing-masing platform dengan mengorbankan performadari response API tersebut baik dari latency, bandwidth maupun data yang disediakan. Penelitian iniakan menerapkan arsitektur GraphQL dalam mengembangkan API yang mampu melayani aplikasi dariberbagai platform, dimana GraphQL dapat mengatasi masalah terkait data yang tersedia dan dibutuhkanaplikasi, penggunaan latency dan bandwidth yang minimal sesuai kebutuhan masing-masing platformserta permasalahan dokumentasi dan versi dari API dengan memanfaatkan fitur-fitur yang disediakanpada arsitektur GraphQL.Kata Kunci: GraphQL, Multi-platform, API, RESTful, latency, bandwidth.